The Antioxidant Activities of the Methanol Extracts of Dischidia nummularia - Yakoba Tari; Theo Da Cunha; Theodore Y. Lulan; Yohanes Buang (Journal of Applied Chemical Science, 2012)
There has been elucidated the antioxidant activities of chloroform and aqueous fract ions of methanol extracts isolated from dischidia nummularia. The study was firstly started by maceration of dischidia nummularia powder in certain quantity of pure methanol solvent and followed by gradual partition of the methanol extract with chloroform and distillated water and then purified with column chromatography. The chemical contents migrated into both those later solvents were detected by GC-MS and their functional groups were detected by FT-IR instruments. Thereafter, the antioxidant activities of the migrated compounds in each those solvents were determined using hydrogen peroxide protocol and the absorbance was read at 240 nm. The ascorbic acid solution was used as control. The results showed that GCMS spectrum indicated the phenol compounds only that are existed within the chloroform and the aqueous fractions of the extract. Furthermore, the FT-IR spectrum showed methylene and ethene groups are existed within those phenol compounds as well as the hydroxyl, carbonyl, aromatic, and keton groups. The average absorbances of compounds contained within the chloroform and aqueous fractions were 0.275 and 0.189, respectively, whereas that of the control was 0.085. Those absorbance data conclusively indicated that higher absorbance higher residue of chromophore content existed within the fraction and higher failures of hydroxylation reactions. Overall, the antioxidant behaviors of the aqueous and chloroform fractions of the dischidia nummularia methanol extracts are contributed by the phenol compounds and the activities of their aqueous fractions are higher than those of the chloroform fractions.